Exploring cognitive function and postoperative neurocognitive recovery after cardiac surgery in older adults (ECPON): a protocol for an observational study - Ulrica Nilsson; Markus Saarijärvi; Lina Bergman; Jeanette Eckerblad; Gabriela Markovic; Ernad Zecevic; Tor Damén; Anna Martinik (BMJ Open)
Introduction Cardiovascular disease is one of the most common health issues facing the older population, and the number of older adults undergoing cardiac surgery is expected to increase. Postoperative neurocognitive impairment is a frequent and often unrecognised complication that can adversely affect a patient’s recovery, quality of life and daily activities, as well as impact the lives of their family members. Patients may express cognitive difficulties as a feeling of ‘not being the same since the operation’. This study aims to investigate the factors that influence neurocognitive function and patient-reported cognitive symptoms among patients aged 65 and older following cardiac surgery, and explore the impact on the overall postoperative recovery. Additionally, the study aims to describe the perspectives of close relatives on the recovery process.Methods and analysis A longitudinal observational study with a mixed-methods approach will be conducted in two thoracic surgical departments in Sweden. A total of 220 patients and 1 close relative for each patient will participate. Neurocognitive function will be assessed preoperatively and at 1, 3 and 6 months postoperatively using a digitalised neurocognitive test battery. We will also evaluate postoperative patient-reported cognitive symptoms and signs, delirium, frailty, health-related quality of life, depression, perceived self-efficacy, fatigue and functional capacity. Each patient’s close relative will assess the observed cognitive function and report on caregiver burden. At the 6-month mark, a purposive sample of patients and their close relatives will be interviewed to explore their experiences of postoperative cognitive recovery.Ethics and dissemination The study has been approved by the Swedish Ethical Review Authority (Reference number: 2024-03380-01) and will adhere to the Helsinki Declaration and its amendments. The results will be disseminated through peer-reviewed journals and scientific conferences, as well as presented in various popular science forums and patient organisations.Trial registration number NCT06469515; Pre-results.